Observation of Taxonomic Features of A Terrestrial Algae Oedocladium Terrestre Biswas (Chlorophyceae) With Soil Analysis From West Bengal, India - Halder, Nilu (Journal of Natural History Museum, 2018)
In the present paper, a brief description along with valuable information of Oedocladium terrestre Biswas, a member of Oedogoniales of Chlorophyta, has been provided. This species was collected from a velvety green patches on damp soil at Jirat of Hooghly district, West Bengal, India. The bending of mature oogonium downwardly was an interesting feature that might be due to easy entry for gametes within this female structure. This character is appeared to be an ecological adaptation for terrestrial habitat. In addition to that, presence of narrower rhizoids in the thallus that helps penetrating, anchoring and absorbing water and mineral contents from soil also supported the terrestrial adaptation of this taxon. This is a rare algal taxon. The soil analysis of the algal distribution site showed the following features as: sand (36.1%), silt (28.1%), clay (35.8%), pH (7.1), EC (0.154 dSm-1), OC (6.7 mgkg-1), Ca2+ (4.8 cmol+kg-1), Na+ (0.72 cmol+kg-1), K+ (0.16 cmol+kg-1), WHC (47%) and total S (98.2 mgkg-1). J. Nat. Hist. Mus. Vol. 29, 2015,, Page: 1-8